NEW VITAMIN C DETERMINATIONS IN MEXICAN FOODS - GIRAL, FRANCISCO (Instituto de Salubridad y Enfermedades Tropicales, Instituto Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
The total lipid of the Mexican orthopteran, S purpurascens Charpentier, consists mainly of free fatty acids, whose approx composition has been detd The fat of Sphenarium (Pyrgomorphidae) does not contain S, a feature in which it differs from that of Me
CIENC MEX
Keywords: VITAMIN, DETERMINATIONS, MEXICAN, FOODS; MULTIDISCIPLINARIA; CIENCIAS DE LA NUTRICION; NUTRIENTES